Asymmetric Decentralization and Peace Building: A Comparison of Aceh and Northern Ireland - Ali Abdurahman; Bilal Dewansyah (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
AbstractThis article compares the asymmetric form of decentralization model in the Aceh, Indonesia, and in the Northern Ireland, the United Kingdom, towards the process of peacemaking. In general, the decentralization models in the two regions have almost similar backgrounds due to prolonged religious conflicts. However, the devolution model in Northern Ireland is far more complex than Aceh’s, and closely related to other countries, that affect the constitutional status of Northern Ireland in the future. This is different from the Aceh government, which since the Helsinki MoU has remained a part of the Indonesia’s unitary form. On the other hand, in terms of governmental matters, decentralization in Aceh reflects a reduction in their special authority, with a pattern of division of government functions that is almost similar to the division of functions in the ordinary regional government. It is in contrast to the affairs of Northern Ireland’s government concerning matters that are categorized traditionally as the exclusive affairs of the central government in a unitary state, such as security matters. This provides a lesson for Indonesia that the issue of federalism in Aceh is indisputable and the Northern Ireland case reinforces the insight that federal state and unitary state have some degrees of similarity.Desentralisasi Asimetris dan Penciptaan Perdamaian: Membandingkan Aceh dengan Irlandia UtaraAbstrakArtikel ini membandingkan model desentralisasi dengan otonomi khusus Aceh, Indonesia dan devolusi di Irlandia Utara, Kerajaan Inggris sebagai bentuk desentralisasi asimetris yang berkorelasi pada penciptaan perdamaian. Secara umum, model desentralisasi di kedua daerah tersebut memiliki kesamaan latar belakang yaitu akibat konflik berkepanjangan. Namun, devolusi di Irlandia Utara jauh lebih kompleks dibandingkan di Aceh karena disebabkan oleh konflik keagamaan yang telah berakar secara historis dan berhubungan erat dengan negara lain yang mempengaruhi status konstitusional Irlandia Utara di kemudian hari. Hal ini berbeda dengan dengan pemerintahan Aceh yang sejak MoU Helsinki tetap menjadi bagian dari Indonesia dalam bentuk negara kesatuan. Di sisi lain, dari segi urusan pemerintahan, desentralisasi di Aceh justru mencerminkan berkurangnya kekhususan Pemerintahan Aceh, dengan pola pembagian urusan pemerintahan yang hampir sama dengan pembagian urusan pemerintahan daerah pada umumnya, berbeda dengan urusan pemerintahan Irlandia Utara yang sangat luas, menyangkut urusan yang secara tradisional dikategorikan sebagai urusan eksklusif pemerintah pusat di negara kesatuan, seperti keamanan. Hal ini memberikan pelajaran bagi Indonesia bahwa antara negara federal dan negara kasatuan memiliki persamaan-persaman dalam derajat tertentu.DOI: https://doi.org/10.22304/pjih.v6n2.a3